Effect of increasing GleptoForte dosage in newborn pigs on sow and litter performance - Knight, Mylah L.; Williams, Hayden E.; Jones, Cassandra K.; DeRouchey, Joel M.; Tokach, Michael D.; Woodworth, Jason C.; Goodband, Robert D.; Dritz, Steven S.; Holtcamp, A. (My University, 2017)
Newborn piglets are likely to develop iron deficiency due to insufficient iron deposits at birth and from extremely high growth rates prior to weaning. This iron deficiency can cause lower numbers of red blood cells circulating, fatigue and death. Therefore piglets need a supplemental iron injection before they reach 3 days old. The most appropriate amount of the injectable iron, Gleptoforte, has not been established and supported by data. The purpose of this study was to evaluate the effects of increasing dosage of Gleptoforte in newborn pigs on sow and litter performance. In a 21 day farrowing study, a total of 336 newborn pigs (DNA 241x600) out of 28 different litters were used in this study; six gilts and six barrows from each litter were chosen. Then, using a completely randomized design pigs were split into 6 different treatments, leaving 56 piglets per treatment. The six different treatments include: 1) control, 2) 50 mg Gleptoforte, 3) 100 mg Gleptoforte, 4) 150 mg Gleptoforte, 5) 200 mg Gleptoforte and 6) 200 mg Gleptoforte plus a 100 mg booster on day 11 of farrowing. The different blood data that was recorded include hemoglobin, hematocrit, serum Fe, and total iron binding capacity (P=0.001). As a whole, average daily gain and ending body weights were higher with increasing dosage of Gleptoforte. Although there was improvement with increasing dosages, there was no significant difference between 200 mg and 200mg with a booster. Blood criteria levels were also higher in piglets that received a higher dose of Gleptoforte. However, there was a significant difference in hemoglobin and serum Fe levels between 200 mg and 200 mg with a booster. A lack of iron injection resulted in the worst growth and blood parameters. While 100mg resulted in the best growth performance, the treatment of 200mg with a booster resulted in the best blood parameters but it did not make the growth performance any better than the 200mg treatment.
Keywords: Fall 2017